PERAMALAN MENGGUNAKAN METODE BACKPROPAGATION NEURAL NETWORK - SAWITRI, MADE NITA DWI; SUMARJAYA, I WAYAN; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika; Vol 7 No 3 (2018)DO - 10.24843/MTK.2018.v07.i03.p213, 2018)
The purpose of the study is to forecast the price of rice in the city of Denpasar in 2017 using backpropagation neural network method. Backpropagation neural network is a model of artificial neural network by finding the optimal weight value. Artificial neural networks are information processing systems that have certain performance characteristics similar to that of human neural networks. This analysis uses time series data of rice prices in the city of Denpasar from January 2001 until December 2016. The results of this research, concludes that the lowest rice price is predicted in July 2017 at Rp9791.5 while the highest rice price in April 2017 for Rp9839.4.